Applied dimensional analysis and modeling - Szirtes, Thomas (Elsevier/Butterworth-Heinemann, 2007)
Applied Dimensional Analysis and Modeling provides the full mathematical background and step-by-step procedures for employing dimensional analyses, along with a wide range of applications to problems in engineering and applied science, such as fluid dynamics, heat flow, electromagnetics, astronomy and economics. This new edition offers additional worked-out examples in mechanics, physics, geometry, hydrodynamics, and biometry. * Covers 4 essential aspects and applications: - principal characteristics of dimensional systems - applications of dimensional techniques in engineering, mathematics and geometry - applications in biosciences, biometry and economics - applications in astronomy and physics * Offers more than 250 worked-out examples and problems with solutions * Provides detailed descriptions of techniques of both dimensional analysis and dimensional modeling.